The Effect of History of Premature Rupture of Membranes and Asphyxia on the Occurrence of Premature Rupture of Membranes at RSIA Aulia Jagakarsa in 2018 - Abela Mayunita; Indah Sri Wahyuni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Premature rupture of membranes is the rupture of the membranes before the birth process occurs, either at term or preterm gestation. The causative factors are incompetent cervix, excessive uterine tension, multiple pregnancies, hydramnios, abnormal membrane physiology, predisposing factors such as parity, maternal age, gestational interval, and nutritional status. Complications that arise can include maternal or neonatal infection, premature delivery, hypoxia, compression of the umbilical cord, fetal deformities, increased incidence of cesarean delivery. The purpose of this study was to determine the effect history of premature rupture of membranes and asphyxia on the incidence of premature rupture membranes at RSIA Aulia Jagakarsa 2018. The descriptive method with a cross-sectional approach was used in this study. The sample was taken using random sampling. The data was collected from the medical record—analysis using a univariate and bivariate test. The results show that respondents with PROM at RSIA Aulia in 2018 were 57 people (65.5%), and 30 people (34.5%) did not experience PROM. A total of 31 (81.69%) respondents with PROM have a history of PROM, and 26 (53.1%) respondents with PROM have no history of PROM. The incidence of asphyxia in patients with PROM was 27 (54%) respondents and as many as 30 (81.1%) without asphyxia despite PROM. From these results, there is a relationship between a history of PROM and the incidence of PROM. However, there is no relationship between asphyxia and PROM.Keywords: Premature rupture of membranes, asphyxia